2018
DOI: 10.1111/cbdd.13345
|View full text |Cite
|
Sign up to set email alerts
|

Inhibiting mechanism of small molecule toward the p53‐MDM2 interaction: A molecular dynamic exploration

Abstract: Disruption of the p53-MDM2 interaction has been an efficient strategy to renew the function of wild-type p53. In this work, molecular dynamic simulations, molecular mechanics-generalized Born surface area method, and principal component analysis were combined to probe interaction mechanism of inhibitors 2TZ, 2U0, 2U1, 2U5, 2U6, and 2U7 with MDM2. The rank of our current predicted binding free energies is in agreement with that of the experimental values. The results demonstrate that the introductions of thiazo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 113 publications
0
4
0
Order By: Relevance
“… 33 , 46 Moreover, various works have been involved in successful insights into binding selectivity of small compounds toward homologous receptors with very similar sequence. 47 52 However, the conformations of receptors sampled by cMD simulations are possibly trapped at a local minimum energy well, 53 which will generate an insufficient structural ensemble and affect statistical rationality. To relieve this sampling issue in cMD simulations, multiple short molecular dynamics simulations (MSMDSs) with various initial conformations are proposed so as to obtain better sampling efficiency than a single long trajectory.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 33 , 46 Moreover, various works have been involved in successful insights into binding selectivity of small compounds toward homologous receptors with very similar sequence. 47 52 However, the conformations of receptors sampled by cMD simulations are possibly trapped at a local minimum energy well, 53 which will generate an insufficient structural ensemble and affect statistical rationality. To relieve this sampling issue in cMD simulations, multiple short molecular dynamics simulations (MSMDSs) with various initial conformations are proposed so as to obtain better sampling efficiency than a single long trajectory.…”
Section: Introductionmentioning
confidence: 99%
“…With rapid development of calculational technology and computer hardware, classical molecular dynamics (cMD) simulations and binding affinity computations increasingly play significant roles in unveiling molecular mechanism and conformational transformations of receptors. In calculations of binding affinity, the entropic computation is highly changing, Duan et al proposed a more efficient method of entropic calculations, namely interaction entropy, which not only obtains rational results but also saves computational time. , Moreover, various works have been involved in successful insights into binding selectivity of small compounds toward homologous receptors with very similar sequence. However, the conformations of receptors sampled by cMD simulations are possibly trapped at a local minimum energy well, which will generate an insufficient structural ensemble and affect statistical rationality. To relieve this sampling issue in cMD simulations, multiple short molecular dynamics simulations (MSMDSs) with various initial conformations are proposed so as to obtain better sampling efficiency than a single long trajectory. , Recently, different works verify that MSMDSs can indeed obtain rational conformational samplings of receptors, moreover MSMDSs have been extensively applied to uncover conformational transformations of receptors, binding selectivity, drug resistance, etc. In the present work, three inhibitors, namely D8Q, D9T, and UO1 were chosen to study their binding selectivity toward BAZ2A/B and decipher selectivity-dependent molecular mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…However, mutational analyses of PPI interfaces revealed that the binding affinity is not evenly distributed across the binding interfaces, but instead contributed by the small patch of amino acid residues know as hot spot . Most of the hot spots are enough compact in size to be filled by the peptide or small molecules . Identification of hot spot residues at the interface by experiments is time consuming and costly.…”
Section: Introductionmentioning
confidence: 99%
“…[25][26][27][28] Most of the hot spots are enough compact in size to be filled by the peptide or small molecules. [29][30][31] Identification of hot spot residues at the interface by experiments is time consuming and costly. Therefore, several computational techniques, such as machine learning approach, molecular docking, and computational alanine scanning, have been developed with high accuracy to predict hot spot residues.…”
mentioning
confidence: 99%